Negative Regulator Nlrc3-like Maintain the Balanced Innate Immune Response During Mycobacterial Infection in Zebrafish - Niu, Liangfei; Luo, Geyang; Liang, Rui; Qiu, Chenli; Yang, Jianwei; Xie, Lingling; Zhang, Kaile; Tian, Yu; Wang, Decheng; Song, Shu; Takiff, Howard E.; Wong, Ka-Wing; et al. (Frontiers in Immunology, 2022)
The NOD-like receptors (NLRs) have been shown to be involved in infection and autoinflammatory disease. Previously, we identified a zebrafish NLR, nlrc3-like, required for macrophage homeostasis in the brain under physiological conditions. Here, we found that a deficiency of nlrc3-like leads to decreased bacterial burden at a very early stage of Mycobacterium marinum infection, along with increased production of pro-inflammatory cytokines, such as il-1β and tnf-α. Interestingly, myeloid-lineage specific overexpression of nlrc3-like achieved the opposite effects, suggesting that the impact of nlrc3-like on the host anti-mycobacterial response is mainly due to its expression in the innate immune system. Fluorescence-activated cell sorting (FACS) and subsequent gene expression analysis demonstrated that inflammasome activation-related genes were upregulated in the infected macrophages of nlrc3-like deficient embryos. By disrupting asc, encoding apoptosis-associated speck-like protein containing a CARD, a key component for inflammasome activation, the bacterial burden increased in asc and nlrc3-like double deficient embryos compared with nlrc3-like single deficient embryos, implying the involvement of inflammasome activation in infection control. We also found extensive neutrophil infiltration in the nlrc3-like deficient larvae during infection, which was associated with comparable bacterial burden but increased tissue damage and death at later stage that could be alleviated by administration of dexamethasone. Our findings uncovered an important role of nlrc3-like in the negative regulation of macrophage inflammasome activation and neutrophil infiltration during mycobacterial infection. This highlights the importance of a balanced innate immune response during mycobacterial infection and provides a potential molecular basis to explain how anti-inflammatory drugs can improve treatment outcomes in TB patients whose infection is accompanied by a hyperinflammatory response.